Peningkatan Hasil Belajar Mata Pelajaran Matematika Dalam Penyelesaian Soal Faktor Persekutuan Terbesar Dengan Menggunakan Model Pembelajaran STAD di SDN 005 Lubuk Baja Batam - Habsoh, Siti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
The purpose of this study was to improve the learning outcomes of mathematics in the material of the 4th grade greatest common factor of elementary school through the STAD learning model. This research is a classroom action research with a collaborative pattern using the Kemmis and Mc Taggart cycle model. The subjects of this study were 4th grade students of SDN 005 Lubuk Baja Batam City. Data collection techniques using observation, interviews, actions and test results. Data analysis used descriptive quantitative. The criteria for success in this study is the percentage of learning completeness reaches 80%. The results showed that the STAD type of learning model could improve mathematics learning outcomes in the 4th grade Elementary Largest Common Factor material. At the time of pre-action, students were only 23% complete and 76.5% were incomplete. In Cycle I, the value of students who completed was 44.1%, and for students who did not complete in Cycle I was 55.9%. In Cycle II the increase in student completeness was very significant, namely 88.3%, but there were still students who were still incomplete by 11.7%. The obtained results provide information that the STAD Learning Model can improve learning outcomes for the Greatest Common Factors material.